Editions : Arakawa - Beuys - Brauntuch - Chia - Christo - Clemente - Cucchi - Goldstein - Haring - Judd - Kounellis - Longo - Merz - Paladino - Salle - Twombly - Warhol : Neue Editionen 1985. - Schellmann & Klüser, München; Schellmann & Klüser, New York (München : Schellmann & Klüser, 1985)
Arakawa ; Beuys, Joseph ; Brauntuch, Troy ; Chia, Sandro ; Christo ; Clemente, Francesco ; Cucchi, Enzo ; Goldstein, Jack ; Haring, Keith ; Judd, Donald ; - Kounellis, Jannis ; Longo, Robert ; Merz, Gerhard ; Paladino, Mimmo ; Salle, David ; Twombly, Cy ; Warhol, Andy
Duits
boek